OPTIMIZATION OF MANAGEMENT APPROACHES: RESERVES GROWTH OF EFFICIENCY OF NR-MANAGEMENT IN THE BUSINESS - F. Sh. Fedorova; E. V. Deshcherevskaya (Модернизация, инновация, развитие, 2017)
The article describes one of the possible ways of building more eff ective relationships between managers and subordinates, taking into account variable range of individual motivation, capabilities and potential of people belonging to diff erent types of employees.The topic is urgent due to the changes in modern business processes that require new approaches to management. Goal/objectives. Our aim is to develop an approach to the creation of human resources management model that takes into account not only the knowledge and skills of employees, but also their deeper individual characteristics. The approach accounts for the hierarchy of one's life values and drives, temperament, strains, habitual and unfamiliar social roles, way of thinking, preferred pattern of communication, peculiarities of the behavior in power relations and a host of other features. We suggest that asking them into account is an incredible opportunity for productivity growth and team eff ectiveness improvements.Methodology. The theoretical basis of the article are studies of Russian and foreign authors on the classifications and typologies of personality, of social roles, roles in the team, as well as subordinate types. The article refl ects the results of studies and observations of the authors on the peculiarities of manifestation of diff erent types of people in decision-making and business communications.Results. We suggest the typology of subordinates describing the key characteristics and preferences of representatives of the types. The typology allows to build relationships between managers and subordinates more eff ectively.Conclusions/significance. We propose typology of subordinates that can be used to develop management models focused on certain types of employees. This, in turn, may be useful for structuring of human management, retrieval of unused but eff ective management tools, and for building an eff ective staff -management relations network as a whole to achieve business targets / KPI.